“Foi a escravidão” : uma arqueologia histórica de duas cadeias de exceção contra povos indígenas em Minas Gerais, Brasil (1968-1979) - Pedro Pablo Fermin Maguire (2022)
Between 1968 and 1979, during the Brazilian Dictatorship (1964-1985) the Military Police of the State of Minas Gerais set up two ‘indigenous prisons’ against indigenous peoples from all over the country. Over 300 prisoners were interned in a regime of exception without legal process, established penal types or defined sentences. The ‘prisons’ operated a regime of terror, forced labour and torture. One person disappeared from them and at least two died as a result of internment. In 2021 a Brazilian judge ruled that they were central in the crime of genocide committed against the Krenak people. This, alongside their illegal character as places of internment, is one of the similarities highlighted between the ‘prisons’ and concentration camps. Prior to the criminal investigation carried out by the Brazilian ombudsman most of the academic research of the ‘prisons’ disregarded both survivors’ testimony and the ruins of the prisons, still standing in the Indigenous Lands they once operated in. This research sought to correct such asymmetries through an archaeology of the ‘prisons’ which, based on survivors’ accounts and the archaeological recording of their materiality, reconstructs their history. From this proposal emerge both a more detailed understanding of the way the ‘prisons’ operated- based on their spatial pattern- and a discussion of the experience which explores the concept of history and temporalities of the two surviving indigenous peoples: the Krenak and the Pataxó.